A new, diminutive, upland Sphenomorphus Fitzinger 1843 (Squamata: Scincidae) from the Belum-Temengor Forest Complex, Peninsular Malaysia - Grismer, L. Lee; Ahmad, Norhayati; Onn, Chan Kin (Zootaxa, 2009)
A new species of diminutive, upland, forest floor skink, Sphenomorphus temengorensis sp. nov. is described from the Belum-Temengor forest complex in northern Peninsular Malaysia. This species is differentiated from all other 36 Sundaland species of Sphenomorphus on the basis of a unique suite of morphological and color pattern characteristics. This is the first reptile known to be endemic to the Belum-Temengor forest complex and underscores the need for additional field research in this area that is actively being logged.